Reliability and Validity Studies of Externality of Happiness Scale Among Turkish Adults - Murat Yildirim; Ufuk Barmanpek; Ahmad A. H. Farag (European Scientific Journal, ESJ, 2018)
Externality of happiness is a psychological construct that refers to the degree to which individuals perceive their level of happiness as beyond their control and mostly dependent to external factors. The aim of this study was to examine the reliability and validity of the Externality of Happiness scale (EOH) among a Turkish adult sample. A total of 230 participants (152 males and 78 females; mean age = 37.8 years, SD = 9.1) completed self-report measures of externality of happiness, life satisfaction, flouring, self-esteem, and fear of happiness. Exploratory and confirmatory factor analysis supported a one-factor structure for the EOH. The EOH was found to be negatively correlated with life satisfaction, flourishing, and self-esteem and positively correlated with fear of happiness. The scale also showed incremental value over self-esteem in predicting life satisfaction. Furthermore, the scale was found to be discriminated from fear of happiness. Moreover, evidence was provided for internal-consistency reliability. Overall, the findings suggested that Turkish version of EOH had adequate reliability and validity scores and that it can be used as a useful measurement tool to assess externality of happiness beliefs in future clinical practice and research.